2021
DOI: 10.1002/alz.12437
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic function of DPP4 in diabetes‐associated mitochondrial dysfunction and cognitive impairment

Abstract: Dipeptidyl peptidase-4 (DPP4) has been proven to exert its functions by both enzymatic and nonenzymatic pathways. The nonenzymatic function of DPP4 in diabetesassociated cognitive impairment remains unexplored. We determined DPP4 protein concentrations or its enzymatic activity in type 2 diabetic patients and db/db mice and tested the impact of the non-enzymatic function of DPP4 on mitochondrial dysfunction and cognitive impairment both in vivo and in vitro. The results show that increased DPP4 activity was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Hyperglycemia possibly leads to hippocampal tissue damage. An animal study ( 144 ) suggested that overexpression of Dipeptidyl peptidase-4 (DPP4) in diabetic rats may reduce peroxisome proliferator-activated receptors γ-Coactivator 1α expression, leading to mitochondrial dysfunction. Hyperglycemia may also increase the levels of inflammatory cytokines, such as interferon-γ (IFN-γ) and interleukin-6 in the hippocampus, resulting in the apoptosis of hippocampal neurons ( 145 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia possibly leads to hippocampal tissue damage. An animal study ( 144 ) suggested that overexpression of Dipeptidyl peptidase-4 (DPP4) in diabetic rats may reduce peroxisome proliferator-activated receptors γ-Coactivator 1α expression, leading to mitochondrial dysfunction. Hyperglycemia may also increase the levels of inflammatory cytokines, such as interferon-γ (IFN-γ) and interleukin-6 in the hippocampus, resulting in the apoptosis of hippocampal neurons ( 145 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that the expression of SIRT1 and PGC-1α in the brain of T2DM mice decreased significantly [120]. Decreased PGC-1α expression and activation in hippocampal neurons of T2DM mice leads to blocked mitochondrial biogenesis and mitochondrial dysfunction, triggers neuronal loss, and promotes cognitive impairment in diabetes [133,134]. Downregulation of PGC-1α in the hippocampus of T2DM may result from dipeptidyl peptidase-4 binding to protease-activated receptor 2 and triggering glycogen synthase kinase-3β (GSK3β) activation [133].…”
Section: Mitochondrial Biogenesismentioning
confidence: 96%
“…Decreased PGC-1α expression and activation in hippocampal neurons of T2DM mice leads to blocked mitochondrial biogenesis and mitochondrial dysfunction, triggers neuronal loss, and promotes cognitive impairment in diabetes [133,134]. Downregulation of PGC-1α in the hippocampus of T2DM may result from dipeptidyl peptidase-4 binding to protease-activated receptor 2 and triggering glycogen synthase kinase-3β (GSK3β) activation [133]. Insulin signaling has also been found to be involved in regulating PGC-1α expression, affecting mitochondrial biogenesis [135,136].…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…It has been indicated that cerebral glucose hypometabolism is associated with an increased risk of DACD (Sun et al, 2021). In this study, 18 F‐FDG microPET was used to detect glucose uptake in the brain in vivo.…”
Section: Resultsmentioning
confidence: 99%